Mothers' intention to vaccinate their daughters against human papillomavirus in NorthWest Ethiopia, using the theory of planned behavior - Samrawit Tilahun; Habtamu Wondiye; Zeamanuel Anteneh Yigzaw (Taylor & Francis Group, 2023)
ABSTRACTHuman papillomavirus (HPV) is the second most common cause of cancer worldwide among females. HPV vaccination is highly protective against HPV infection and can reduce 56% of HPV infections. Therefore, the study aims to assess mothers' intention to vaccinate their daughters aged 9-14 years old against human papillomavirus in Debre Tabor town, Northwest Ethiopia, using the theory of planned behavior. A community-based cross-sectional study design was employed using the theory of planned behavior from November 1 to 30, 2022, in Northwest Ethiopia. A total sample of 449 study participants was enrolled. The study participants were selected using a multi-stage random sampling technique. Data was collected using an interview-administered questionnaire. The data was entered into EPI data version 4.6 and then, exported to SPSS version 23 for analysis. Those variables with a p-value <.05 with 95% CI were considered significant predictors. Mothers' positive intention to vaccinate their daughters aged 9-14 years against HPV was 67.5%. Attitude, perceived behavioral control, and subjective norm were significant predictors with (AOR = 10.09, 95% CI = 6.23-16.32), (AOR = 4.12, 95% CI = 2.71-6.26), and (AOR = 16.397, 95% CI = 9.69-27.748), respectively. Only two-thirds of mothers have a positive intention to vaccinate their daughters against human papillomavirus. Attitude, perceived behavioral control, and subjective norm were predictors. Therefore, it is better to do community mobilization toward the advantage of HPV vaccination.